Relevansi carbon emission disclosure dan karakteristik perusahaan pada perusahaan yang terdaftar di Jakarta Islamic Index - Bayu Tri Cahya (Faculty of Economics, Universitas Islam Indonesia, 2017)
AbstractThis study aimed to analyze the influence of corporate’s characteristics toward carbon emission disclosure and disclosure of carbon emission effect toward firm value. Companies characteristics variable are proxied by firm size, profitability and leverage. The sampling method is a company incorporated in the Jakarta Islamic Index (JII) which amounted of 34 companies. The data used in this study is the annual reports of each companies obtained through the Indonesia Stock Exchange and the hypotheses were tested using multiple regression analysis. The results of this study indicate that the leverage proven that is has significant negative effect toward disclosure of carbon emissions, while profitability and size of the company doesn’t have significant influence. Finally, the disclosure of carbon emissions are significantly influence the value of the company.